POLA AKTIVITAS KOMUNIKASI INDIVIDU PERUSAHAAN PT KARYA TEKHNIK UTAMA PADA MASA PANDEMI COVID-19 - Dita, Risqiana Dita Febrianti; Kundori (SCIENTIA JOURNAL, 2022)
The Covid-19 pandemic greatly affects all aspects of human life, especially the running of an organization, one of which is PT. Karya Tekhnik Utama. Communication is the key to how PT. Karya Tekhnik Utama can survive and coexist with Covid-19. Communication that is carried out within an organization is called organizational communication, where in organizational communication there is a communication pattern. The purpose of this study was to see how the communication patterns that occurred during the Covid-19 pandemic at PT. Karya Tekhnik Utama uses Goldhaber Organizational Communication Theory. In Goldhaber Organizational Communication Theory, there are seven key stages of communication that need to be considered in organizational communication. The seven keys are process, message, network, relationship, interdependence, environment and uncertainty. This study used descriptive qualitative methods and data collection in this study was conducted by interview and observation. The results showed that the communication patterns that occurred during the Covid-19 pandemic at PT Karya Tekhnik Utama were formal and informal communication, direct and indirect communication, and the communication network pattern formed was the free channel or star communication network pattern.